Roles, challenges and solutions of the orphanage caregivers on their care work in Kota Bharu Kelantan - Nurul Hidayah Zulkipli (2018)
A person who takes care of the orphanage is described as caregivers. They are responsible towards every aspect of the orphans'life and development. This study aimed to investigate the challenges faced by the orphanage caregivers in performing their duty as an orphanage caregiver. Qualitative research was used in this study. Non-participant observation and in-depth interview session were conducted in gaining the information from caregivers.